Programa “Amigos de los árboles” y su influencia en las actitudes de protección de las plantas en niños/as del 5to grado de primera de la I.E N°00123 de Segunda Jerusalén - Gonzáles Chuque, Claudia (2010)
The present denominated investigation programs Friends of the trees he/she has had as general objective to improve the attitudes of protection of the plants by means of the application of the program Friends of the trees in children and girls of the fifth degree of Primary Education, area science and atmosphere of the Educational lnstitution N° 00123 of Second Jerusalem of the .county of Rioja. This study is justified for its relevancy and convenience, since the proposal contributes to improve the attitudes conservationist's of the children and girls especially toward the plants of its environment; for their social transcendences since it serves like programmatic instrument of organized activities with the firm purpose of changing indifferent attitudes for favorable attitudes toward the plants; also he/she will have methodological utility, indeed, the results benefitted to family parents and community in general, in the sense that their children and integral of the society they will be the main characters in this improvement of the man's relationship - it plants; finally he/she is ..a ttributed a practica! justification, since he/she intends to promote the environmental education, and for en de to optimize the attitudes toward the conservation and protection of the plants of our environment and in that way to elevate the quality of life and to propitiate a better environmental future for the children and girls. The program Friends of the trees was systematized keeping in mind the theory of the action reasoned according to FISHBEIN and AJZEN (1975), the theory of the naturalistic intelligence according to GARDNER (1983) and the principies of the environmental education according to Mary NOVO (1996), besides other theoretical contributions that were good usas antecedents for the investigation. Supported in these theories, he/she thought about the altemative hypothesis in the following terms: lf the program Friends of the trees is applied", then he/she will improve the attitudes of protection of the plants significantly in the children and girls of the flfth degree of Primary Education of the Educational lnstitution N° 00123 of Second Jerusalem. The sample taken for the study was conformed by a group control and an experimental group constituted by two sections of the fifth degree, 34 children and girls of the section TO and 34 children and girls of the section " 8 " the same ones that were chosen aleatorily, for he/she was carried out it the purification of the variable interveners. To the elected sample, he/she was administered a pre test to evaluate the level of attitudes that the children and girls possessed subsequently before the application of the program Friends of the trees the three phases of the proposed program they were developed: conceptual-instructive phase, phase demonstrative-applicative and vivencialextensive phase by means of the planned learning sessions. After having culminated this period, the search test was administered, so much to the group control as to the experimental group to determine the effects taken place by the program Friends of the trees in the experimental group. Once obtained the data, you proceeded to the analysis and respective interpretation of the same ones, being demonstrated that the application of the program Friends of the trees improved the attitudes of protection of the plants significantly in the three components: cognitive, emotional and conduction, passing of unfavorable attitudes (1 average = 8,5} to favorable attitudes (1 average = 14,4) in the children and primary girls of fifth level degree of the Educational lnstitution N° Second 00123 Jerusalem.